Tumor suppressor genes - Bunz, Fred (Henry Stewart Talks, 2021)
Oncogenes and their history, Tumor suppressors genes, Contrast between oncogenes and tumor suppressor genes, Tumor suppressor genes and the two-hit hypothesis, Retinoblastoma and RB1 as a tumor suppressor gene, p53 as a tumor suppressor gene, Important tumor suppressors that regulate the cell cycle, Inherited vs. sporadic cancers